2021
DOI: 10.3389/fgene.2021.697549
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That the Etiology of Congenital Hypopituitarism Has a Major Genetic Component but Is Infrequently Monogenic

Abstract: PurposeCongenital hypopituitarism usually occurs sporadically. In most patients, the etiology remains unknown.MethodsWe studied 13 children with sporadic congenital hypopituitarism. Children with non-endocrine, non-familial idiopathic short stature (NFSS) (n = 19) served as a control group. Exome sequencing was performed in probands and both unaffected parents. A burden testing approach was used to compare the number of candidate variants in the two groups.ResultsFirst, we assessed the frequency of rare, predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…In this study, each patient was found to harbor three possible causative gene variants, after WES. Although to date numerous studies have shown that CPHD as well as PSIS have an oligogenic rather than a monogenic etiology [11,12,[63][64][65], such a conclusion could not be reached in this work.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In this study, each patient was found to harbor three possible causative gene variants, after WES. Although to date numerous studies have shown that CPHD as well as PSIS have an oligogenic rather than a monogenic etiology [11,12,[63][64][65], such a conclusion could not be reached in this work.…”
Section: Discussionmentioning
confidence: 58%
“…However, the etiology of approximately 85% of the cases still remains unknown [3]. Furthermore, various studies demonstrated that the genetic causes of CPHD and pituitary stalk interruption syndrome (PSIS) are oligogenic rather than monogenic [11][12][13]. Similarly, congenital hypogonadotropic hypogonadism (CHH) is now considered as an oligogenic disease, and it has been shown by various studies that mutations in genes associated with CHH may also be related with CPHD, PSIS and holoprosencephaly, indicating a genetic overlap between these syndromes [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some family members with the variants, which lead to an abnormal pattern of transcripts, showed no phenotype or attenuated phenotype ( 34 , 45 ). In congenital hypopituitarism, previous studies suggested oligogenic inheritance ( 59 , 60 ), which may also apply to these POU1F1 variant carriers.…”
Section: Discussionmentioning
confidence: 85%